Effect of Beauveria bassiana and Metarhizium anisopliae on the growth of Spodoptera frugiperda by seed inoculation - JELLY MILINIA PUSPITA SARI; SITI HERLINDA; SUWANDI SUWANDI; ELFITA ELFITA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sari JMP, Herlinda S, Suwandi S, Elfita. 2023. Effect of Beauveria bassiana and Metarhizium anisopliae on the growth of Spodoptera frugiperda by seed inoculation. Biodiversitas 24: 2350-2357. Spodoptera frugiperda J.E.Smith 1797 larvae are more difficult to control because they hide in the leaf sheaths. Therefore, it is necessary to use endophytic entomopathogenic fungi to control S. frugiperda larva. The aim of this research was to observe the effect of endophytic Beauveria bassiana (Bals.-Criv.) Vuill. and Metarhizium anisopliae (Metschn.) Sorok?n on the growth of S. frugiperda larvae by seed inoculation. A total of six isolates of B. bassiana (5 isolates) and M. anisopliae (1 isolate) were isolated from infected-host insect corpses and identified molecularly. The corn seeds were immersed using a fungal suspension of 1 x 1010 conidia mL-1. The results showed that feeding on maize leaves colonized with B. bassiana (JGTP240521A, WTTJC260521A, WTTJC290521A, WTTJC290521B, and JGNT300521 isolates) and M. anisopliae (WTTJC260521B isolate) significantly reduced the larval and pupal weight. The highest mortality (above 50%) of S. frugiperda larvae was recorded by B. bassiana (JGTP240521A isolate) . The treated larvae could produce abnormal and malformation pupae and adults, increasing mortality. Both fungi killed the larvae and induced disruption of normal growth larvae, pupae, and adults of S. frugiperda. B. bassiana was more pathogenic than M. anisopliae in killing the larvae of S. frugiperda. Results revealed that endophytic fungi B. bassiana and M. anisopliae inoculated through seed treatment had a negative impact on the growth of S. frugiperda larvae. Further studies are needed on the effect of B. bassiana and M. anisopliae by foliar spraying or seed treatment on maize plant to control S. frugiperda in the field.